Sabine MacCormack's Legacy in the Andes - Maqque, Víctor (2019)
Dr. Sabine MacCormack, a historian of Classics and of the Andes, left her extraordinary library to the Instituto Pastoral Andina (IPA) in Perú. Professor MacCormack was recognized by her exemplary scholarship, her books, and numerous articles examining the complex history of colonial Andes. Her trajectory from Germany to England, and then to the United States was as significant as the scope of her studies from the classic Greco-Roman to the Andean world. Her colleagues and friends on mourning her tragic death reflected on the importance of a comprehensive intellectual inquiry into the seemingly detached societies that MacCormack studied. The contributions of MacCormack, however, continue thriving on the number of followers of her studies and her carefully collected and curated library that is now located in Peru.